Factors affecting the composition of long-chain fatty acids in the African buffalo (Syncerus caffer) - Webb, E.C. (Edward Cottington) (University of Pretoria, 2013)
Dissertation (MSc Agric (Production Physiology))--University of Pretoria, 2000.